Os direitos sociais e as políticas públicas: possibilidades e limites de sua efetivação por meio da ação civil pública - Mousinho, Ileana Neiva (2005)
The research undertakes an analysis of the possibilities of the social rights concretization which are understood by state material services (health, education, social assistance, labor, living, integral protection to children, adolescents, handicapped people, the elderly etc) through the use of judicial means. In this line, it is shown that the social rights, once ascertained in the Federal Constitution, has immediate applicability, forcing the state to implement measures corresponding to public ruling, aiming at its adequate execution. The effectiveness of the social rights depends on a hermeneutic commitment with the Democratic Law of State, which directs the state actuation for the promotion of human dignity. In this way, through interpretation, immediate efficacy to the social rights and the existence of public rights is given and are subjected to concretization of the corresponding part of the minimum existential understood as a gathering of necessary services for a dignified existence, without the impediments opposed by the possible reservation theory. It is demonstrated that the public civil action is a capable instrument foreseen constitutionally, for the legitimate – specifically Public Minister and associations – to postulate judicially the implementation of political measures or their correction, when wrongly planned which may interfere with the constitutional principals that should guide the administrative action. In face of the objectives that the Democratic Law of State can propose and of the mechanisms of popular participation foreseen in the Constitution – among which the public civil action is outstanding – the judicial determination for the administrator to implement social rights concretized public measures or to correct them, does not interfere with the separation of power, nor does it constitute an exaggerated exercise of a damaging judicial activism, but only, the answer to the Judicial Power is obliged to give society – considered its irrenounceable Power of state – in fulfillment of the fundamental rights of ample access to the Jurisdiction. One is faced still with the allusive question to the legitimacy from the Public Ministry to postulate, and from the Judicial Power to determine, the implementation of public measures, concluding that the legitimacy of both is absorbed by the own constitution, as well as, given concretely, by the head of the public power – the people – when it exerts - the right to provoke the actuation of the Parquet, with visits of estimation of the public civil action. In face of the de legitimacy in which the public administrators who go against the constitution incur, it is legitimated that the Judicial is take decisions through force of the normative and political-constitutional structure of the organization, taking into consideration technical knowledge, necessary to the work subministered by the civil society.